Association between Takayasu’s arteritis and active tuberculosis in a child: A case report - Koreti, Sunita; Verma, Y S; Patel, G S (Indian Journal of Child Health, 2015)
Takayasu’s arteritis (TA) is an autoimmune disease that affects large arteries. A possible relationship between TA and tuberculosis (TB) has been suggested as both diseases have similar chronic inflammatory lesions and occasionally granulomas in the arterial walls. TA commonly presents with cardiac involvement and rarely with sole presentation of ischemic stroke. Response with anti-tubercular drugs and steroid has been well-documented. Only a few studies have been published on TA with TB in children. We present a case of a 9-yearold boy who was presented with low-grade fever, persistent headache, vomiting, and abnormal body movements and on further workup was diagnosed as a case of active TB with TA.